Dendritic cell activation by an E. coli-derived monophosphoryl lipid A enhances the efficacy of PD-1 blockade. (1st March 2020) - Jeong, Youngmin; Kim, Gi Beom; Ji, Yuhyun; Kwak, Gi-Jung; Nam, Gi-Hoon; Hong, Yeonsun; Kim, Seohyun; An, Jinsu; Kim, Sun Hwa; Yang, Yoosoo; Chung, Hak Suk; Kim, In-San
Abstract: Cancer immunotherapy is a powerful approach for cancer treatment, but its clinical effects rely on the tumor's immune conditions. In particular, low response rates to PD-1 blockades are highly correlated with impaired T cell priming. Here, we demonstrate that E. coli -derived monophosphoryl lipid A (EcML) activates dendritic cells in a toll-like receptor-4 (TLR-4)-dependent manner and increases the sensitivity of cancer cells to anti-PD-1 immunotherapy. EcML is a mixture of 4′-monophosphoryl lipids A (MPLAs) produced directly by an engineered Escherichia coli strain; it has a unique congener composition that differentiates it from the well-established MPLA adjuvants, 3-O-desacyl-4′-monophosphoryl lipid A and glucopyranosyl lipid A. Given that active dendritic cells initiate adaptive immune responses, we investigated the anti-tumor activity of an aqueous formulation of EcML. Upon sensing EcML via TLR-4, dendritic cells matured into powerful antigen-presenting cells that could stimulate naïve T cells. EcML reduced tumor growth in the B16F10 mouse model via dendritic cell activation and potentiated PD-1 blockade therapy in the B16F10-OVA melanoma model. These data identify EcML as a promising TLR-4 agonist that can induce anti-tumor immune responses and potentiate PD-1 blockade therapy against tumors. Highlights: E. coli -derived monophosphoryl lipid A (EcML) directly activates dendritic cells in a toll like receptor-4-dependent manner. EcML is a mixture of 4′-monophosphoryl lipids A (MPLAs) produced directly by an engineered Escherichia coli strain. Aqueous formulated EcML elicits strong adjuvant activity and reduces tumor growth in the B16F10 syngenic mouse model. EcML plus anti-PD1 antibody combination provides potent tumor-specific T cell immune responses in the B16F10-Ova model.